(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article describes the socio-psychological climate, factors that influence its perception, in particular, anxiety, presents the types of socio-psychological climate and presents the results of a study of the personal anxiety of the student group (by C. Spielberg) and its impact on the socio-psychological climate (by A. Fidler). The results of the study are highlighted, how the students’ personal anxiety influences the perception of the social and psychological climate in the group.